2021
DOI: 10.3390/vaccines9030201
|View full text |Cite
|
Sign up to set email alerts
|

Access to Vaccination Information and Confidence/Hesitancy towards Childhood Vaccination: A Cross-Sectional Survey in China

Abstract: Access to vaccination information could influence public attitudes towards vaccination. This study investigated the number and types of vaccination-related information sources, and estimated their associations with vaccine confidence and hesitancy in China. In January 2019, we conducted a cross-sectional survey in China, and 2122 caregivers with children <6 years completed self-administered questionnaires. Logistic regressions were used to assess associations between caregivers’ primary information sources … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
25
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(29 citation statements)
references
References 48 publications
4
25
0
Order By: Relevance
“…Furthermore, it is noteworthy that the most popular source of COVID-19 related information among the study population are television, radio and social media, rather than, for example, governmental sources and healthcare workers (figure 2), which is in line with recent literature 27. Previous research has shown that individuals who inform themselves mostly relying on social media as primary source of information are more likely to be hesitant than those drawing more on professional sources of information 28. Thus, as shown by research concerned with other health topics, such as reproductive health, HIV and other sexually transmitted infections, social media needs to be used more effectively as a tool to communicate correct and appropriate information about COVID-19 vaccinations 29 30…”
Section: Discussionsupporting
confidence: 82%
“…Furthermore, it is noteworthy that the most popular source of COVID-19 related information among the study population are television, radio and social media, rather than, for example, governmental sources and healthcare workers (figure 2), which is in line with recent literature 27. Previous research has shown that individuals who inform themselves mostly relying on social media as primary source of information are more likely to be hesitant than those drawing more on professional sources of information 28. Thus, as shown by research concerned with other health topics, such as reproductive health, HIV and other sexually transmitted infections, social media needs to be used more effectively as a tool to communicate correct and appropriate information about COVID-19 vaccinations 29 30…”
Section: Discussionsupporting
confidence: 82%
“…This can be explained by comparing to other countries such as France and Italy, which indicate that beliefs in vaccine efficacy have emphasized the importance of severity, susceptibility, benefits, perceived barriers, and trust or distrust in biomedical research associated with the vaccine. 7 , 29 In sum, potential vaccine efficacy conveyed through professional information sources that address vaccine concerns, clarify misinformation, and disseminate evidence-based information increase confidence and safety in the population, 30 raising the likelihood of vaccinating and protecting others as a collective responsibility, and including children. 31 In view of this, the authorities must effectively convey public health messages so that the population voluntarily accepts a vaccine against severe COVID-19 disease.…”
Section: Discussionmentioning
confidence: 99%
“…However, for the public, it is challenging to determine authentic and valid facts in the vast pool of available information. Transparent and accurate information is essential for rebuilding vaccine confidence ( 22 ). In addition, it is necessary to understand the public's sources of information and improve the efficiency of information transmission.…”
Section: Introductionmentioning
confidence: 99%